Leadership in Public Sector Management: Perceptions of International Residents in Lublin, Poland - Pariyar, Om Prakash (Journal of Multidisciplinary Research Advancements, 2025)
This study examines leadership practices in public sector management through the lens of international residents in Lublin, Poland, combining theoretical insights from public administration literature with empirical survey data. The research addresses a significant gap in understanding how leadership styles, particularly transformational and transactional approaches, impact service quality and user satisfaction for non-native populations in Eastern Europe. The study employs a mixed-methods approach, beginning with a review of leadership theories to establish a conceptual framework. It then analyses survey responses from 113 international students in Lublin, assessing their experiences with public services across 12 indicators, including transparency, communication, accessibility, and facility quality. Key findings reveal a disparity between institutional objectives and user perceptions. While digital payment systems and physical infrastructure were rated positively (mean scores of 3.60 and 3.35, respectively), language barriers and unclear processes were major pain points (25% rated communication as "very poor"). The results highlight the limitations of rigid bureaucratic systems in accommodating diverse populations and underscore the need for adaptive, emotionally intelligent leadership.